EVALUATION OF CROWDSOURCING APPLICATION ON GOJEK DRIVER JOB SATISFACTION IN SURABAYA - Amiyantho, Eko; Wulandari, Sri Hariani Eko; Wardhanie, Ayouvi Poerna (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2019)
PT. Gojek Indonesia is one of the nation's startups that is successful and has an impact on the economy in Indonesia today. In its business the company is engaged in online transportation services by disseminating its business concepts to the wider community by utilizing information technology called the crowdsourcing model concept. By disseminating the work it will have many drivers that are managed to be prone to cause problems of job dissatisfaction, among others, the use of illegal applications to do work, select incoming orders, not friendly and impolite in serving customers, drivers using fake GPS applications. The impact if the driver's job dissatisfaction is allowed to drag on is to damage Gojek's service image, customers turn to other competitors, and dissatisfied drivers will switch to other online transportation applications. In overcoming the problem, it is necessary to hold a research that discusses the current problems by using the concept of crowdsourcing on job satisfaction. This study aims to determine the level of job satisfaction of drivers, knowing satisfaction with the application, and providing application recommendations for the future.